Assessing testing rates for viral hepatitis B and C by general practitioners in Flanders, Belgium: a registry-based study. Issue 5 (9th May 2019) - Bielen, Rob; Koc, Özgür M; Busschots, Dana; Robaeys, Geert; Aertgeerts, Bert; Vaes, Bert; Mamouris, Pavlos; Mathei, Catharina; Goderis, Geert; Nevens, Frederik
Abstract : Objectives: Chronic infections with hepatitis B virus (HBV) and hepatitis C virus (HCV) have a major impact on mortality worldwide. Although effective treatments are available for both HBV and HCV infection, <50% of the patients are even diagnosed in Belgium. This study assessed the real-life testing—and diagnosis rate by general practitioners (GPs) in Flanders, Belgium. Setting: We assessed the testing rate for HBV and HCV in 48 primary care practices with electronic medical records linked into one central registry in Flanders, Belgium. Participants: The registry contains data of 440 140 patients over 20 years, which corresponds to 2.2% of the total Flemish population yearly. The primary care practices are distributed across Flanders and the patient population is representative for the distribution of age, gender and socioeconomic status at the community level. Results: Of 440 140 patients included in the registry, 7892 (1.8%) patients were screened for hepatitis B surface antigen (HBsAg) and 7206 (1.6%) for hepatitis C antibody (HCV Ab) of whom 369 (4.7%) and 163 (2.3%) tested positive, respectively. Of 14 059 patients with chronic liver enzyme elevation, 1112 (7.9%) and 1395 (9.9%) were tested for HBsAg and HCV Ab, respectively. There was no improvement in testing rates over time. Conclusions: This study demonstrates that real-life testing uptake for viral hepatitis B and C is suboptimal in the general practices in Flanders, even in patients with chronically elevated liver enzymes. As GPs play a crucial role in prevention, diagnosis and linkage to care, efforts and strategies to increase the testing uptake for HBV and HCV are urgently needed.